The stability of articulated tipping trailer units - Pickering, Simon Gilchrist (1994)
When an articulated tipper unit is being loaded or is tipping, it is unlikely to be standing on perfectly level ground. Also, the centre of gravity of the load is unlikely to be in the centre of the body. Hence the loads carried by the suspension and tyres on one side of the tipper will be greater than those on the other side. This uneven loading will cause the tyres and suspension on one side of the tipper unit to deform more than those on the other side. It will also cause the chassis to deform; the twisting about its longitudinal axis being the most significant mode of deformation. As a result of these deformations caused by the uneven loading, the position of the centre of gravity will be shifted even further towards the more heavily loaded side. This will cause even more uneven loading and further deformations.